Identification of Key Performance Indicators related to the implementation of a hybrid energy supply system based on renewable energy sources. Issue 1 (May 2021) - Tuţică, D; Sandu, M R; Pătraşcu, R; Ionescu, C
Abstract: Complex energy systems need to evaluate their performance through the achievement of its own objectives but also by comparison with best practices. This can be realized by identifying the key performance indicators (KPI) that clearly monitor the progress towards project goals. The work focuses mainly on the identification and categorisation of KPIs through a quantitative approach for the case of implementation of a hybrid energy supply system into the existing district heating network of University Politehnica of Bucharest. The main results of the study show that two levels of KPI can be defined: technology specific and overall DHC system. If on the technology level, the approach is to use the specifics standards already existing for the main technologies, for the system level, little information is available and consequentially, a method for calculating separately the cooling and heating impact in terms of energy, environment, and economy is proposed.